Blood Chemical Analysis in Children with Acute Gastroenteritis, When Is It Useful? - Tavakolizadeh, Reza; Sadeghi, Manelie; Namiranian, Nasim; Fahimi, Daryoosh; Barkhordari, Mohammad (Journal of Pediatric Nephrology, 2013)
Introduction: Acute gastroenteritis (AGE) is one of the most common diseases in children. Intravenous (IV) fluid therapy may be indicated in some of them. The aims of this study were to assess the usefulness of blood chemical analysis (blood glucose, urea, creatinine, sodium, potassium and bicarbonate) and to define any clinical criterion that helps to predict usefulness before starting IV fluid therapy. Materials and Methods: A cross sectional study was conducted at the Emergency Department of Bahrami Children Hospital from March 2011 to June 2012; all children with AGE who were between 3 months to 10 years without any underlying diseases were enrolled in the study. Demographic variables, medical history and physical examination, laboratory tests results, and dehydration grading (according to the World Health Organization criteria) were noted. The usefulness of laboratory tests was defined as any change in the treatment plan due to laboratory results. Results: Four hundred and fifty nine children (55.3% boys, 44.7% girls, mean age 25.36 months) were assessed. There were statistically significant associations between the usefulness of tests and patients’ age, frequency of passing diarrheal stool in the last 24 hours, and dehydration grade (p<0.001). Only dehydration grade could significantly predict usefulness according to a logistic regression model (p<0.05). Conclusions: According to these results, routine blood chemical analysis may be useful in patients with moderate to severe dehydration. Keywords: Gastroenteritis; Child; Blood Chemical Analysis